Percy Jackson's Greek gods - Riordan, Rick.; Rocco, John (Los Angeles : Disney/Hyperion Books, 2014)
Percy Jackson, a modern-day demigod, tells the origin stories of the gods of Olympus and provides an insider's point of view--with plenty of attitude--in this illustrated collection.
Includes bibliographical references and index.
School Library Journal, October 2014.
Voice of Youth Advocates (V.O.Y.A.), October 2014.
Kirkus Review, July 2014.
5.1
3-6
Keywords: Jackson, Percy, -- (Fictitious character) -- Fiction; Jackson, Percy, -- (Fictitious character) -- Fiction; Gods, Greek -- Fiction; Jackson, Percy (Fictitious character) -- Fiction; Gods and goddesses -- Greece -- Fiction; Gods, Greek -- Fiction; Mythology -- Fiction